A SURVEY ON THE IDENTIFIABILITY OF FINITE MIXTURES - B. SETIAWATY (Dept. of Mathematics, IPB University, 2004)
This paper is a survey on the identiﬁability of ﬁnite mixtures. We collect all the results regarding suﬃcient conditions for ﬁnite mixtures to be identiﬁable and what kind of distributions family which is identiﬁable.